A systemic risk assessment methodological framework for the global polycrisis - Ajay Gambhir; Michael J. Albert; Sylvanus S. P. Doe; Jonathan F. Donges; Nadim Farajalla; Leandro L. Giatti; Haripriya Gundimeda; Sarah Hendel-Blackford; Thomas Homer-Dixon; Daniel Hoyer; Sumaya Adan; David Jacome-Polit; et al. (Nature Communications)
Abstract Human societies and ecological systems face increasingly severe risks, stemming from crossing planetary boundaries, worsening inequality, rising geo-political tensions, and new technologies. In an interconnected world, these risks can exacerbate each-other, creating systemic risks, which must be thoroughly assessed and responded to. Recent years have seen the emergence of analytical frameworks designed specifically for, or applicable to, systemic risk assessment, adding to the multitude of tools and models for analysing and simulating different systems. By assessing two recent global food and energy systemic crises, we propose a methodological framework applicable to assessing systemic risks in a polycrisis context, drawing from and building on existing approaches. Our framework’s polycrisis-specific features include: exploring system architectures including their objectives and political economy; consideration of transformational responses away from risks; and cross-cutting practices including consideration of non-human life, trans-disciplinarity, and diversity, transparency and communication of uncertainty around data, evidence and methods.